2008
DOI: 10.1007/978-3-540-69387-1_67
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Regularization in Scalefree-Trees of Coupled 2D Chaotic Maps

Abstract: Abstract. The dynamics of coupled 2D chaotic maps with time-delay on a scalefree-tree is studied, with different types of the collective behaviors already been reported for various values of coupling strength [1]. In this work we focus on the dynamics' time-evolution at the coupling strength of the stability threshold and examine the properties of the regularization process. The time-scales involved in the appearance of the regular state and the periodic state are determined. We find unexpected regularity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Within each cluster nodes oscillate between two groups of points, firstly as a quasi-periodic orbit, and later as a periodic (regular) orbit (see ref. [18]). Also, studies of our CMS on smaller graphs (motifs) [5] revealed strange attractors as node-orbits, some of which appear to have the properties of the strange non-chaotic attractors [19].…”
Section: Coupled Chaotic Maps On Treesmentioning
confidence: 93%
“…Within each cluster nodes oscillate between two groups of points, firstly as a quasi-periodic orbit, and later as a periodic (regular) orbit (see ref. [18]). Also, studies of our CMS on smaller graphs (motifs) [5] revealed strange attractors as node-orbits, some of which appear to have the properties of the strange non-chaotic attractors [19].…”
Section: Coupled Chaotic Maps On Treesmentioning
confidence: 93%
“…Recently, the topology of a social network was inferred using mobile phone data [8]. Invasive reconstruction methods involve perturbing the network dynamics which allows for structural data to be easily extracted [9]. Although invasive methods generally give good results, it is often unpractical to interact with the on-going network dynamics.…”
Section: Introductionmentioning
confidence: 99%